Akulturasi Islam dan Budaya Sunda: Kajian Sejarah Arsitektur Tajug Masjid Agung Cirebon - Supendi, Usman; Zamani, Afiat Fahma; Siroj, Muhammad Rifqi Niam; Berutu, Irfan Syafai; Aziz, Abdul (Ideas Publishing, 2024)
Tajug is a traditional architectural form from Java-Sunda, specifically used for religious buildings. However, this term is becoming increasingly unfamiliar to modern society. This study traces the historical development of tajug to explore the symbols embedded in the tajug of the Sang Cipta Rasa Grand Mosque in Cirebon, serving as a case study for this research. Utilizing historical research methods—heuristics, criticism, interpretation, and historiography—the findings reveal that tajug symbolizes the harmony between Islamic traditions and Sundanese culture, reinforcing identity and serving as a spiritual symbol in society. This article explains how the use and preservation of tajug can help sustain Islamic values within Sundanese cultural practices.